Therapeutic alternatives for COVID-19 - Pareja Cruz, Arturo (2020)
In December 2019, China became the center of a pneumonia outbreak of unknown cause that caught the world’s attention. It was the new coronavirus 2019 (2019-nCoV or SARS-CoV-2), which has rapidly spread to the rest of the world. As of March 31, 2020, around 800,000 cases and 38,714 deaths have been reported worldwide. In Peru, 950 cases and 24 deaths have been reported. The virus has been found to affect most frequently elderly people, immunocompromised individuals or those with comorbidities. In this review article, we offer a comprehensive overview of current knowledge related to therapeutic alternatives for COVID-19, from drugs with proven antiviral activity that have been regularly used in other pathologies (arbidol, remdesivir, lopinavir/ritonavir, favipiravir) to drugs that have been usually used as antiparasitic (chloroquine and hydroxychloroquine) or antibacterial agents (teicoplanin and azithromycin), but nowadays have gained notoriety because of their possible and potential efficacy against COVID-19. Likewise, the therapeutic schemes recently included in the technical standard issued by the Ministry of Health of Peru (chloroquine, hydroxychloroquine and hydroxychloroquine/azithromycin) are highlighted. Although significant advances have been achieved in determining potential therapeutic alternatives, randomized controlled trials are needed to determine the safety and efficacy of medications for the treatment of patients with COVID-19.